Помогите упростить выражение

0 голосов
42 просмотров

Помогите упростить выражение


image

Алгебра (35 баллов) | 42 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1) (b² + 81)/(b - 12)(b + 12) + 6/(b + 12) =
 (b² + 81 + 6b - 72)/(b - 12)(b + 12) =  (b² +  6b + 9)/(b - 12)(b + 12)  = 
= (b + 3)² /(b - 12)(b + 12) 
2) [(b + 3) / (b - 12)] : [ (b + 3)² /(b - 12)(b + 12) ] =
= [(b + 3)*(b - 12)(b + 12)] /[ (b - 12)(b + 3)²= (b + 12) / ( b+ 3)

(61.9k баллов)
0 голосов

1)(b²+81)/(b-12)(b+12)+6/(b+12)=(b²+81+6b-72)/(b²-144)=(b²+6b+9)/(b²-144)=
=(b+3)²/(b²-144)
2)(b+3)/(b-12):(b+3)²/(b²-144)=(b+3)/(b-12)*(b-12)(b+12)/(b+3)²=(b+12)/(b+30